Peran Kepala Sekolah dan Interaksi Sosial terhadap Kinerja Guru melalui Komitmen Bersama pada Sekolah Dasar Negeri di Kecamatan Serang Kota Serang - Sunarni, Ani; Suparna, Dade; Hardianto, Ade Manggala (Penerbit Goodwood, 2024)
Purpose: Good teacher performance will influenced the quality students, and quality education achieved with good teacher quality, good teacher quality. This study aimed to build a teacher performance model with joint commitment mediation involving ASN teachers. Research methodology: The research method was quantitative with the statistical tool structural equation model (SEM) PLS. The research population consisted of teachers (79 respondents). Results: The results indicated 1) a significant influence of the principal’s role on teacher performance. 2) Social interaction had a significant influence on teacher performance. 3) The principal has a significant influence on joint commitment. 4) Social interaction has a significant influence on joint commitment. 5) Joint commitment had an insignificant influence on teacher performance. Limitation. The limitation of the research sample is that it only describes a local scale. As for future researchers, may developed role of teacher loyalty and the impact of increasing certification allowances as a moderating variable Contribution: Factors that directly influence teacher performance include the role of the principal and social interaction.